2010
DOI: 10.1590/s1413-78522010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Análise biomecânica do equilíbrio do idoso

Abstract: OBJETIVO: Analisar as características biomecânicas do equilíbrio dos idosos, com base na oscilação do centro de pressão em cinco posições de colocação dos pés, com olhos abertos e fechados. Participaram da amostra vinte idosos sendo que para aquisição dos dados utilizou-se a plataforma de força extensométrica amti® or6-5, com freqüência de 100hz durante 60s. MÉTODOS: Processou-se a filtragem dos dados com fft butterworth de 4ª ordem e passa baixa de 20 hz e aplicou-se os testes estatísticos de kruskal wallis e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 3 publications
1
5
1
11
Order By: Relevance
“…Our results corroborate others studies (Brooke-Wavell, Perrett, Howarth, & Haslam, 2002;Cruz, Oliveira & Melo, 2010) that analyzed the CoP displacement in the AP and ML directions, and that observed that the visual feedback is an important contribution to replace reduced somatosensory and vestibular sensory input in older individuals, especially during one-foot stance tasks (Deyer & Ashton-Miller, 1999). In addition, for Soares (2010), the importance of vision increases gradually with the advancing of age, becoming a key factor for the stability of older people.…”
Section: Discussionsupporting
confidence: 92%
“…Our results corroborate others studies (Brooke-Wavell, Perrett, Howarth, & Haslam, 2002;Cruz, Oliveira & Melo, 2010) that analyzed the CoP displacement in the AP and ML directions, and that observed that the visual feedback is an important contribution to replace reduced somatosensory and vestibular sensory input in older individuals, especially during one-foot stance tasks (Deyer & Ashton-Miller, 1999). In addition, for Soares (2010), the importance of vision increases gradually with the advancing of age, becoming a key factor for the stability of older people.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, an unchanged visual information is an important component of the postural control system for maintaining body balance (23). However, the results of the SOT I showed the greatest variation between the groups in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…No presente estudo, foi observado que na variável Unipodal e POMA, em que esses sistemas eram postos à prova, observou-se que no GE houve melhora significativa comparada ao GC no pós-teste. De acordo com Cruz et al, 5 esta melhora se justifica pela contribuição visual na manutenção do equilíbrio e tem explicação na tendência da força de acoplamento entre informação visual e oscilação postural.…”
Section: Discussionunclassified
“…3,4 Um dos componentes intrínsecos do idoso que o predispõe a quedas é a diminuição do equilíbrio ou do controle postural. 2,5,6 Este requer manutenção da gravidade sobre a base de sustentação durante situações estáticas e dinâmicas, sendo que o corpo deve ser capaz de responder às translações do centro de gravidade imposta voluntária ou inesperada, como em um tropeço. 6,7 Uma possibilidade terapêutica de recurso não convencional de reabilitação que vem sendo empregada atualmente na fisioterapia é a realidade virtual.…”
Section: Introductionunclassified